1978
DOI: 10.1021/jm00203a008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of neuronal monoamine uptake. 2. Selective inhibition of 5-hydroxytryptamine uptake by .alpha.-amino acid esters of phenethyl alcohols

Abstract: A series of alpha-amino acid esters of substituted phenethyl alcohols was prepared and tested as inhibitors of the neuronal reuptake of noradrenaline and 5-hydroxytryptamine. Some of the compounds are potent and very selective in blocking the 5-hydroxytryptamine uptake, as evidenced by biochemical data and behavioral tests. The most promising agent, alaproclate [2-(4-chlorophenyl)-1,1-dimethylethyl 2-aminopropanoate hydrochloride (I, IV)], was selected for further studies as a potential antidepressant agent. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“…Indeed it was found that the antagonism of the harmaline-induced increase in cGMP in cerebellum in vivo was obtained in the same dose range (5-20 mg/kg) that alaproclate inhibits 5-HT uptake in vivo (Ogren e t al. 1984) which is in accordance with the similar in vitro affinities of alaproclate for the NMDA channel binding site (Ki=0.5 pM in hippocampus) (Svensson & Ross 1995) and for the 5-HT uptake site (Ki=0.13 pM in hippocampal synaptosomes) (Lindberg et al 1978).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Indeed it was found that the antagonism of the harmaline-induced increase in cGMP in cerebellum in vivo was obtained in the same dose range (5-20 mg/kg) that alaproclate inhibits 5-HT uptake in vivo (Ogren e t al. 1984) which is in accordance with the similar in vitro affinities of alaproclate for the NMDA channel binding site (Ki=0.5 pM in hippocampus) (Svensson & Ross 1995) and for the 5-HT uptake site (Ki=0.13 pM in hippocampal synaptosomes) (Lindberg et al 1978).…”
Section: Discussionsupporting
confidence: 78%
“…The 5-HT uptake inhibitory action of alaproclate does not seem to be involved in the antagonism of the NMDA receptor-stimulated cGMP production since the alaproclate analogue GEA-857, that causes very weak if any inhibition of 5-HT uptake in vitro and in vivo (Lindberg et al 1978, Ogren e t al. 1992), was at least as potent as alaproclate in antagonizing the harmaline-induced increase in cGMP Both of these compounds block K+ channels (Hedlund 1987;Hedlund & Andersen 1989;Hedlund & Ogren 1992) but this ability does not seem to be involved in the effect examined in the present study since the unselective K+-channel blocker 4-aminopyridine in the contrary to alaproclate and GEA857 per se caused a pronounced increase in cGMP Furthermore, Svensson e t al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of a 5-HT uptake inhibitor, alaproclate, and a 5-HT direct agonist, quipazine, on cocaine self-administration were characterized to determine whether serotonergic modulation of the behavioral-stimulant effects of cocaine reported previously extends to its reinforcing effects. Alaproclate has high nanomolar affinity for the 5-HT transporter and greater than 50-fold selectivity for the 5-HT transporter compared with DA and norepinephrine transporters (Lindberg et al, 1978). Quipazine is a nonselective 5-HT agonist with low nanomolar affinity for 5-HT 2 binding sites (Glennon, 1986).…”
mentioning
confidence: 99%